A cross-sectional study on school-age children living near a municipal waste incinerator: Urinary metal levels and renal impairment assessment. (February 2020) - Xu, Peiwei; Wu, Lizhi; Chen, Yuan; Xu, Dandan; Wang, Xiaofeng; Fu, Qiuli; Chen, Zhijian; Lou, Xiaoming; Lou, Jianlin
Abstract: To take an insight into the long-term accumulation of chromium (Cr) and cadmium (Cd) in school-age children living near an MWI and to assess their early renal impairment, we conducted a cross-sectional study in 2015. A total of 116 children from the exposure area and 122 from the control area were recruited. We measured the urinary levels of Cr (U–Cr) and Cd (U–Cd) by inductively coupled plasma mass spectrometry (ICP-MS), and detected three classic renal tubule indicators, including N -acetyl-β-d -glucosaminidase (NAG), β2-microglobulin (BMG), and retinol binding protein (RBP). The U–Cd and U–Cr levels in children living near the MWI were 0.11 and 1.57 μg/g creatinine, respectively. Both the U–Cd and U–Cr levels in the exposure group were lower than those in the control group, although only U–Cd showed a statistical difference ( p < 0.01). The U-NAG and U-RBP levels in the exposure group were also statistically lower than those in the control group (0.80 vs. 1.74 IU/g creatinine, 0.26 vs. 0.48 mg/g creatinine, respectively). The U–Cd level in this study was positively correlated with the U-NAG level (r = 0.26, p < 0.01), as the U–Cr level was also positively correlated with the levels of U-NAG, U-RBP, and U-BMG (r = 0.21, 0.33, 0.18, p < 0.01, respectively). This study indicates that children living close to this particular MWI may not suffer considerable long-term accumulation of Cd or Cr, nor early renal impairment. Graphical abstract: Image 1 Highlights: Children living around MWIs may not suffer considerable long-term accumulation of Cd or Cr. No distinct early renal impairment was found in these children. The U–Cd levels were positively correlated with the U-NAG levels. The U–Cr levels were positively correlated with the levels of U-NAG, U-RBP, and U-BMG. Abstract : Main finding :Children living in proximity to MWIs may not suffer considerable long-term Cd or Cr accumulation, nor early renal impairment.